2007
DOI: 10.1017/s0007114507798926
|View full text |Cite
|
Sign up to set email alerts
|

Asian plantain (Plantago asiatica) essential oils suppress 3-hydroxy-3-methyl-glutaryl-co-enzyme A reductase expressionin vitroandin vivoand show hypocholesterolaemic properties in mice

Abstract: Asian plantain (Plantago asiatica) essential oil (PAEO) contains multiple bioactive compounds, but its potential effects on lipid metabolism have not been examined. PAEO was found to be mostly composed of oxygenated monoterpenes, with linalool as the major component (82·5 %, w/w), measured using GC -MS. Incubation of 0 -200 mg PAEO/ml with HepG2 cells for 24 h resulted in no significant toxicity. Incubation with 0·2 mg PAEO/ml altered the expression of LDL receptor (þ 83 %; P,0·05) and 3-hydroxy-3-methyl-gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…Among effective pharmacological agents in treating these diseases, we can refer to statins, clofibrates and niacin. However, in general these compounds are not effective in reducing cholesterol concentration and are often associated with adverse effects and drug toleration, [12][13][14][15][16][17][18][19]. Therefore, all efforts have been concentrated on prevention strategies like phytochemical diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among effective pharmacological agents in treating these diseases, we can refer to statins, clofibrates and niacin. However, in general these compounds are not effective in reducing cholesterol concentration and are often associated with adverse effects and drug toleration, [12][13][14][15][16][17][18][19]. Therefore, all efforts have been concentrated on prevention strategies like phytochemical diet.…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids are among the essential compounds in herbal oils that induce hypolipidemic effects by inhibiting liver biosynthesis and formation of cholesterol nucleus in bile. Studies have shown that the essential oil compounds of Plantago asiatica inhibit mRNA and protein expression of HMG-COA reductase in HePG2 cells and C57BL/6 cells in rats [19].…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids from herbal essential oils produced hypolipidemic effects by inhibiting hepatic cholesterol biosynthesis and cholesterol nucleation in bile. We showed that Plantago asiatica essential oil suppressed the mRNA and protein expression of HMG-CoA reductase in both HepG2 cells and C57BL/6J mice (8); that MOEO 4 produced antidiabetic effects, improving glucose tolerance and regulating the hepatic expression of genes involved in gluconeogenesis (9); and that wormwood (Artemisia princeps) essential oil displayed potent antioxidative and hypocholesterolemic activities (10). Among plant sources of essential oils, MO is a well-known medicinal herb that has been used for a long time and has been suggested to be effective in the treatment of multiple conditions, including headaches, gastrointestinal disorders, nervousness, and rheumatism (11).…”
Section: Introductionmentioning
confidence: 91%
“…On average, a cup of MO tea (0.15 L) contains~10 mg/L of essential oil (14); accordingly, drinking 2-3 cups of MO tea (0.3-0.45 L) daily may improve metabolic parameters such as plasma cholesterol and TG levels in humans (9). Evidence exists that herbal essential oils have various pharmacological effects that can be attributed to the volatile and terpenoid compounds they contain, which include geranial, cineol, linalool, and caffeic acid (8)(9)(10)16).…”
Section: Introductionmentioning
confidence: 99%
“…Researches are ongoing to define the preventive and curative properties of these natural materials such as Hoveniadulcis, 1) Plantagoasiatica L. seeds, 2) and the fruits of Chrysanthemum indicum Linné, 3) Meliatoosendan fruit, 4) and Schisandrachinensis Baill. 5) Above all, Korean ginseng, the root of Panax ginseng, has been prescribed as the most precious folk medicine in many oriental nations.…”
Section: Introductionmentioning
confidence: 99%